FRI0339 B cell repopulation kinetics after rituximab treatment in anca-associated vasculitides compared to rheumatoid arthritis, and connective tissue diseases: a longitudinal observational study on 120 patients. (15th June 2017) - Thiel, J; Rizzi, M; Troilo, A; Salzer, U; Venhoff, A; Lorenzetti, R; Voll, R; Venhoff, N
Abstract : Background: B cell depletion with rituximab (RTX) is approved for treatment of rheumatoid arthritis (RA) and ANCA-associated vasculitides (AAV). Recently, RTX has been shown to be effective in AAV maintenance therapy, but an optimal RTX treatment schedule is unknown and the time to B cell repopulation after RTX has not been studied. Objectives: To compare kinetics of B cell repopulation after RTX treatment in AAV, RA and connective tissue diseases (CTD) to improve the design of RTX-retreatment schedules in AAV and other autoimmune diseases. Methods: Retrospective single-center analysis of patients with AAV, RA or CTD treated with RTX and a follow-up of >9 months were included. B-cell-repopulation was defined as a peripheral B-cell count >0.5% and >5/μl. Prolonged B cell depletion was defined by a B cell repopulation starting later than 12 months after RTX treatment. Results: 120 patients were included in the study. Sixty-six patients had AAV with 55 classified as granulomatosis with polyangiitis (GPA) or microscopic polyangiitis (MPA) and 11 as eosinophilic granulomatosis with polyangiitis (EGPA). Thirty-five patients had RA and 19 were treated with RTX because of CTD. There were no significant differences between the groups regarding age and sex. Most patients were treated with RTX 1000mg twice, two weeks apart. Cumulative CYC doses were higher in patients with AAV or CTD than in RA patients. In RA and CTD we observed a B-cell repopulation in all patients (100%) while only 33 AAV patients (50%) had started B-cell repopulation (p<0.0001). 93% of the RA and 88% of the CTD patients showed a normal repopulation within the first 12 months after RTX compared to only 10% in GPA and 0% in EGPA (p<0.0001). Mean time to repopulation was significantly longer in GPA/MPA (21 months) and in EGPA (20 months) compared to RA (8.5 months) and CTD (8.7 months). Median time of persistent depletion was 26 months in GPA/MPA, 21 months in EGPA compared to 9 months in RA and 8 months in CTD (p<0.0001). In 25 AAV patients B cell depletion persisted longer than 24 months (mean time 4.4±18.1 years). In ten of 55 GPA/MPA patients B-cells were still depleted 4 years, in six patients even after more than 5 years after only one RTX treatment cycle. One patient had a complete B cell depletion even 8 years after the second RTX treatment. Immunoglobulin production was affected by RTX-treatment with a significant decrease in IgG, IgA and IgM compared to baseline values in GPA/MPA, but not in RA or CTD. In EGPA only IgM declined significantly. Significantly more patients with GPA/MPA and EGPA developed a hypogammaglobulinemia (IgG<7g/L, IgM<0.4g/L). In some AAV patients hypogammaglobulinemia became clinically relevant and required IVIG treatment. Conclusions: In contrast to RA and CTD, in AAV RTX induces long-lasting depletion of B cells that is associated with decreased antibody production. This observation points towards potential defects in the B cell compartment in AAV and has important implications for the design of maintenance treatment schedules using RTX. Disclosure of Interest: J. Thiel Consultant for: Roche, M. Rizzi: None declared, A. Troilo: None declared, U. Salzer: None declared, A. Venhoff: None declared, R. Lorenzetti: None declared, R. Voll Consultant for: Roche, N. Venhoff Consultant for: Roche